All-in-one piezoresistive-sensing patch integrated with micro-supercapacitor. (November 2018) - Song, Yu; Chen, Haotian; Chen, Xuexian; Wu, Hanxiang; Guo, Hang; Cheng, Xiaoliang; Meng, Bo; Zhang, Haixia
Abstract: Portable and wearable sensors have attracted considerable attention, which could perceive and respond to ambient stimuli accurately. For the sake of solving the limited power supply and low integration, it is critical to develop and combine functional electronics with flexible energy devices. In this work, we designed an all-in-one sensing patch integrated with piezoresistance sensor and micro-supercapacitor with the porous CNT-PDMS elastomer. Taking the advantage of porous structure with piezoresistivity and elastomer with electrochemical performance, the piezoresistance sensor shows high sensitivity (0.51 kPa −1 ) and wide detection range as functional fraction, and micro-supercapacitor maintains excellent areal capacitance and cycling stability after 6000 cycles as energy storage fraction, respectively. Assembled with piezoresistance sensor and micro-supercapacitor, the sensing patch could be easily attached on the epidermal skin for joint and muscle monitor with the corresponding resistance response. With high sensitivity and mechanical robustness, such sensing patch could be further utilized as a 3D touch in user identification and safety communication through feature parameter extraction and signal decoding. After packaged into the sensing patch matrix, it could be achieved for static pressure sensing and dynamic tactile trajectory. Therefore, the all-in-one sensing patch shows feasibility in real-time pressure recognition and human-machine interfaces. Graphical abstract: An all-in-one sensing patch is integrated with piezoresistance sensor and micro-supercapacitor based on the porous CNT-PDMS elastomers. The porous CNT-PDMS elastomer is synthesized with solution-evaporation method, which could be modulated by the sugar templates and content ratio. Such piezoresistance-sensing patch could be utilized as 3D touch in user identification and safety communication through parameter extraction and signal decoding. Packaged into the sensing matrix, it shows feasibility in spatially mapping resolved pressure information about static pressure sensing and dynamic tactile trajectory. fx1 Highlights: All-in-one patch is integrated with piezoresistance sensor and micro-supercapacitor. CNT-PDMS elastomer is prepared with mechanical durability and electrical stability. All-in-one sensing patch works as 3D touch in user identification and communication. Sensing matrix shows feasibility in static pressure sensing and dynamic tactile trajectory.